Perlindungan Hukum Investor Terhadap Produk Investasi Emas Di Pegadaian (Studi Pada PT. Pegadaian (Persero) Cabang Kisaran) - Fernando Enrico Fermi Partahi; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Iuris Studia: Jurnal Kajian Hukum, 2021)
Legal protection is needed by every investor in investing in a company. The gold investment in the form of gold tubes is no exception at PT. Pegadaian (Persero) Range Branch. The problems discussed are legal protection for investors who invest in gold from gold investment losses, the responsibility of gold investment management companies for losses experienced by investors, the application of law related to protection of gold investors at PT. Pegadaian (Persero) Range Branch. The research method uses a normative juridical legal research method, which refers to legal norms. This research is descriptive analytical. The data used is secondary data. consists of primary legal materials, secondary legal materials, and tertiary legal materials. The data collection technique is library research (library research). Data analysis is qualitative. Based on the research results obtained, it shows that legal protection for investors who invest in gold from losses on gold investments is carried out in two forms. Namely preventive legal protection and repressive legal protection. The responsibility of the gold investment management company and gold investor begins when they agree to sign the agreement. The company's responsibility for losses suffered by investors is that the company is responsible for these losses due to information that is not in accordance with the agreement. The application of law related to the protection of gold investors, namely gold savings at PT. Pegadaian (Persero) Kisaran Branch is carried out in accordance with the laws and regulations. The forms of legal protection are preventive and repressive. Agreement between legislation. The forms of legal protection are preventive and repressive. The agreement between the company and the investor is a standard agreement that has been provided by PT. Pegadaian (Persero) Kisaran Branch